A new definition of sarcopenia in patients with cirrhosis undergoing liver transplantation. Issue 2 (6th January 2017) - Golse, Nicolas; Bucur, Petru Octav; Ciacio, Oriana; Pittau, Gabriella; Sa Cunha, Antonio; Adam, René; Castaing, Denis; Antonini, Teresa; Coilly, Audrey; Samuel, Didier; Cherqui, Daniel; Vibert, Eric
Abstract : Although sarcopenia is a common complication of cirrhosis, its diagnosis remains nonconsensual: computed tomography (CT) scan determinations vary and no cutoff values have been established in cirrhotic populations undergoing liver transplantation (LT). Our aim was to compare the accuracy of the most widely used measurement techniques and to establish useful cutoffs in the setting of LT. From the 440 patients transplanted between January 2008 and May 2011 in our tertiary center, we selected 256 patients with cirrhosis for whom a recent CT scan was available during the 4 months prior to LT. We measured different muscle indexes: psoas muscle area (PMA), PMA normalized by height or body surface area (BSA), and the third lumbar vertebra skeletal muscle index (L3SMI). Receiver operating characteristic curves were evaluated and prognostic factors for post‐LT 1‐year survival were then analyzed. PMA offered better accuracy (area under the curve [AUC] = 0.753) than L3SMI (AUC = 0.707) and PMA/BSA (AUC = 0.732), and the same accuracy as PMA/squared height. So, for its accuracy and simplicity of use, the PMA index was used for the remainder of the analysis and to define sarcopenia. In men, the better cutoff value for PMA was 1561 mm 2 (Se = 94%, Sp = 57%), whereas in women, it was 1464 mm 2 (Se = 52%, Sp = 91%). A PMA lower than these values defined sarcopenia in patients with cirrhosis awaiting LT. One‐ and 5‐year overall survival rates were significantly poorer in the sarcopenic group (n = 57) than in the nonsarcopenic group (n = 199), at 59% versus 94% and 54% versus 80%, respectively ( P  < 0.001). In conclusion, pre‐LT PMA is a simple tool to assess sarcopenia. We established sex‐specific cutoff values (1561 mm 2 in men, 1464 mm 2 in women) in a cirrhotic population and showed that 1‐year survival was significantly poorer in sarcopenic patients. Liver Transplantation 23 143–154 2017 AASLD